Queer Domesticities - Cook, M. author. aut Link
XIII, 326 p.
Keywords: Sissy home boys or domestic outlaws? Through a series of vivid case studies taken from across the late nineteenth and twentieth centuries, Matt Cook explores the emergence of these trenchant stereotypes and looks at how they play out in the home and family lives of queer men.